Radical Politics - Shepard, Paul (The Trumpeter, 2015)
On March 23rd, 2014, the editors of The Trumpeter received a letter from Florence R. Shepard, Paul Shepard’s widow, regarding her discovery of a short, previously unpublished essay of Paul’s. To our knowledge, it was written in 1995 before he was overcome by the illness that would take his life on July 16th, 1996. We do not know if the essay, entitled “Radical Politics,” was intended as an editorial, if it was sent out at the time or rather abandoned or lost, or if it can be found in his archived papers at Yale. While the essay itself does not in any way overturn his body of published work, we thought it provided an excellent opportunity for exploring anew the political implications of his thought. Rather than publish the piece alone in a standard issue of The Trumpeter, we invited a number of scholars familiar with Shepard’s work to use the essay as a springboard to engage with any aspect of the essay they found to be provocative. Indeed, we hope that this issue will open the door to further and sustained reflection on the directions Shepard’s thought may inspire.